An investigation into the thermal conductivity of hydrating sprayed concrete. (15th October 2016) - Li, Shuangxin; Jones, Benoît; Thorpe, Roger; Davis, Martin
Highlights: Early age thermal conductivity is mainly influenced by free water content. Mature age thermal conductivity is mainly influenced by porosity. Thermal conductivity is found to exponentially vary with density. Abstract: Information about the thermal conductivity of sprayed concrete is useful for calibration exercises using sprayed panels, where heat flows need to be estimated, and future enhancements to the method to include estimates of concrete temperature across the thickness of the lining. However, the necessary information about thermal conductivity of sprayed concrete is rare, and no information about the early age thermal conductivity of sprayed concrete has been found. The thermal conductivity of sprayed concrete aging from five hours after casting to 20 days was continuously measured by a transient method. Thermal conductivity was found to be higher than expected at early age and decreased to the mature value as the concrete cured. Based on these results it is hypothesized that early age thermal conductivity is mainly influenced by free water content, while at a mature stage the key determinants are the structural features of the cement matrix. Thermal conductivity is discovered to have an exponential relationship with density, regardless of mix constituents. A convenient numerical approach is proposed to estimate thermal conductivity for concretes and its accuracy has been verified by data from tests on a wide range of concretes with density ranging from 0.2 g/cm 3 to 2.5 g/cm 3 .